Koordinasi Relay Proteksi Gangguan Hubung Singkat Menggunakan ETAP - Matthew Steven Tarigan; Rizky Wiyugo (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
In electrical power systems, short circuit faults are one of the main causes of equipment damage and widespread power outages when the protection system fails to operate selectively. Therefore, proper coordination between the Over Current Relay (OCR) and Ground Fault Relay (GFR) is essential to ensure reliable and effective system protection. This study aims to analyze the coordination of protection relays against short circuit faults in a 20 kV distribution network using the ETAP software. The research stages include modeling the power system through a single-line diagram, performing load flow analysis, short circuit fault analysis, and relay coordination simulation. The simulation results show that in the initial condition (existing setting), the coordination curves of the relays overlap, which may cause incorrect relay operation sequences. After performing relay resetting in ETAP, the coordination curves between the OCR and GFR no longer overlap, and the operating time complies with the IEEE 242 standard, ranging from 0.2 to 0.4 seconds. Thus, the resulting protection coordination meets the selectivity and reliability criteria, minimizing outage areas and effectively protecting equipment from the impacts of short circuit faults